ANGLE-SPECIFIC CHANGES IN ECCENTRIC HAMSTRING TORQUE AND HAMSTRING TO QUAD RATIO FOLLOWING SIMULATED SOCCER. Issue 7 (11th March 2014) - Cohen, D; Zhao, B; Okwera, B; Martyn, M; Delextrat, A
Abstract : Background: Soccer-specific fatigue decreases eccentric peak torque and the functional peak hamstring to quadriceps torque ratio ( f Hecc :Qcon ), changes thought to increase the risk of hamstring strain (HS). Inadequate eccentric muscle strength specifically at long length may also be a risk factor for HS. The effect of simulated soccer on the hamstring eccentric torque-angle profile, or the hamstring:quad torque ratio at specific joint angles has not been reported. Objective: To determine the effect of a simulated soccer on angle-specific eccentric hamstring torque and angle-specific.Hecc :Qcon (AS.Hecc :Qcon ) across the range of motion. Design: Acute intervention. Setting: Semi-professional soccer. Participants: 9 male players. Risk factor assessment: Isokinetic concentric and eccentric knee flexion and concentric knee extension was evaluated in the dominant limb at 120°·s −1 pre and post the Loughborough Intermittent Shuttle Test (LIST). Main outcome measurements: Changes in eccentric hamstrings torque, concentric quadriceps torque and hamstring:quadriceps torque ratios at 9 joint angles (AS.Hecc :Qcon ), angle of peak torque (APT), and f Hecc :Qcon . Results: The LIST resulted in significant decreases in eccentric hamstring torque at 60˚, 50˚ and 10˚ and a significant (21.8%) decrease in AS.Hecc :Qcon at 10˚ (P<.05). Eccentric hamstring APT increased significantly (P<.05) from 7.1˚to 18.8˚. Conclusions: Simulated soccer produces angle-specific changes in hamstring eccentric torque and in AS.Hecc :Qcon and a shift in the eccentric hamstring APT. Our findings suggest that a prevention programs should both increase fatigue resistance in the hamstrings and include exercises that specifically develop long-length eccentric hamstring strength. Further research is also needed to determine if the evaluation of angle-specific.Hecc :Qcon improves the predictive power of injury risk screening over assessment of the peak torque f Hecc :Qcon alone.